Diasporic consciousness in the material culture of Brazilian Candomblé - Jallo, Zainabu (Routledge studies in anthropology, 2025)
"This book examines Candomblé's material culture and its relationship with the evolving cultural politics of Brazil. It employs artefacts as analytical tools to trace the emergence of a diasporic consciousness. By tracing the movements of artefacts historically, the study reveals how Candomblé has transitioned from a secluded sacred tradition marked by discrimination and persecution to inclusion in the construction of a new cultural character in Brazil. While maintaining its esoteric traditions and contending with ongoing discrimination, the Candomblé sphere has evolved into a confluence of socio-religious and political features expressed in sacred and spectacular contexts. This research highlights the crucial role of artefacts in the various stages of Candomblé's transformation. It demonstrates how diasporic communities progressively exercise political and cultural significance within new societal contexts. The book will be of interest to a broad audience, including scholars from anthropology, material culture studies, art history, history, and religious studies"--